The lazarists of Cosme Velho: educational policy and practice in Rio de Janeiro in two times - Jefferson de Almeida Pinto (Revista Maracanan, 2023)
This article starts from a set of documents from the National Information Service (SNI) whose target was Colégio São Vicente de Paulo, located in the Cosme Velho neighborhood in Rio de Janeiro. Some teachers and students appear in the documentation, which is now disqualified as a center of agitation and political ideas linked to communism. Based on these data, we problematize the article taking into account that the trajectory of the Lazarists in Brazil was understood in the 19th century precisely because of its conservative aspects. The study of the documentation showed how this change in the pedagogical proposal of the school of the Lazaristas took place and how it was received mainly in the midst of a middle class that used its educational services in the context of the Brazilian civil-military dictatorship and its political opening in the years 1980.